Mechanical and tribological properties of CNTs coated aramid fiber-reinforced epoxy composites - Singh M.; Dodla S.; Gautam R.K. (My University, 2025)
This study primarily emphasizes the coating process of carbon nanotubes (CNTs) onto aramid fiber and investigates the subsequent effects of coating on the tribological, mechanical, and thermo-physical characteristics. CNTs and the aramid fibers are oxidized with the combination of sulphuric and nitric acids treatment. The chemical treatments resulted in an increased density of functional groups such as CO, COOH, and OH on the activated surface of the aramid fibers and CNTs. The tribological experiments involve four different normal loads (30 N, 40 N, 50 N, and 60 N), sliding frequencies (6 Hz, 8 Hz, 10 Hz, and 12 Hz), and temperatures (30 °C, 40 °C, 50 °C, and 60 °C). Each experiment runs for 20 min, using a fixed stroke length of 1.5 mm. The worn surfaces are analyzed using SEM images. It was observed that the CNTs-coated aramid fiber enhances the mechanical interlocking between the fibers and the matrix material, due to which the specific wear rate was reduced by 32.41 %, and the tensile strength, modulus, hardness, and thermal conductivity were increased by 23.3 %, 22.9 %, 27.27 %, and 36.56 % respectively. The friction coefficient increases with the increase of the normal load, while it decreases with the rise in temperature or sliding frequency. © 2024